The little engine that could - Piper, Watty; Santat, Dan; Parton, Dolly (New York : Grosset & Dunlap, 2020)
The kindness and determination of the Little Blue Engine have inspired millions of children around the world since the story was first published in 1930. Cherished by readers for ninety years, The Little Engine That Could is a classic tale of a little engine that, despite her size, triumphantly pulls a train full of wonderful things to the children waiting on the other side of a mountain.
This anniversary edition features the original text, all-new reimagined artwork and an introduction from Caldecott Medal-winner Dan Santat, and a special letter from Dolly Parton, award-winning singer-songwriter and founder of Dolly Parton's Imagination Library.
Dolly Parton's Imagination Library.
540L
520L
Decoding demand: 75 (high) Semantic demand: 74 (high) Syntactic demand: 97 (very high) Structure demand: 78 (high)
Accelerated Reader AR
Keywords: Cooperativeness -- Juvenile fiction; Self-confidence -- Juvenile fiction; Railroad trains -- Juvenile fiction; Friendship -- Juvenile fiction; Cooperativeness -- Fiction; Self-confidence -- Fiction; Railroad trains -- Fiction; Friendship -- Fiction; Picture books